Pitch ready for shipment, La Brea Village, Trinidad, B.W.I. - (:unkn) unknown (D. Adamson, Stationer, Port of Spain, 2009)
Photo of two men at the La Brea Village, Trinidad, preparing pitch for shipping. One man is standing by a cart laden with pitch.
Colour: Black and White; Style: Landscape; other: Unbordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Pitch; Asphalt industry--Trinidad and Tobago; Shipping--Trinidad and Tobago; Buildings--Trinidad and Tobago; [1900]; Transportation--Trinidad and Tobago; Carriages and carts--Trinidad and Tobago; Employees--Trinidad and Tobago; Men--Trinidad and Tobago; Draft animals--Trinidad and Tobago; Work; Working class--Trinidad and Tobago; Blue collar workers--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--La Brea; Buildings--Trinidad and Tobago; Clothing and dress--Trinidad and Tobago; Hats--Trinidad and Tobago; Pitch Lake, The (La Brea)